GUGAT CERAI DIKALANGAN MASYARAKAT DI KENAGARIAN BATU BULEK KECAMATAN LINTAU BUO UTARA KABUPATEN TANAH DATAR PROVINSI SUMATERA BARAT GUGAT CERAI DIKALANGAN MASYARAKAT DI KENAGARIAN BATU BULEK KECAMATAN LINTAU BUO UTARA KABUPATEN TANAH DATAR PROVINSI SUM - Bayu Anggara; Acmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Divorce is a disconnection between husband and wife because of certain reasons in households that resulted in disharmony in the household which led to the separation. Divorce is a common phenomenon that occurs in the community, especially in the domination by women who sued for divorce her husband. The difference in the condition of society today is different from the people of old, these changes greatly affect the public's view of divorce.The purpose of this study was to determine the cause of the divorce and to explain how their condition after being widowed in Kenagarian Batu Bulek. This study is useful as an overview and reference in the process of divorce in the home life of the community in Kenagarian Batu Bulek and become a benchmark in the search for and formulate the causes of divorce.Location of the study, the authors will discuss women as plaintiffs in Kenagarian Batu Bulek. To obtain the data, the writer used census data collection techniques with in-depth interviews. The data obtained were processed in a descriptive qualitative analysis.From the results of this study found that the economic factors which became the largest factor causing the divorce in Kenagarian Batu Bulek, while the second factor is the moral and then the third factor is the respondent husband's infidelity.From the above facts it can be concluded that divorce caused by economic factors, generally they have difficulties in life as a single parent women, furthermore, divorce caused by moral factors, they are able to perform the role as a single parent women and divorce caused by infidelity there is one respondents were able to perform the role as a female single parent and one respondent was not able to run it.Keywords: Divorced Petition, Social Change, Women Batu Bulek